Enzyme induction with antiepileptic drugs: Cause for concern?. Issue 1 (27th September 2012) - Brodie, Martin J.; Mintzer, Scott; Pack, Alison M.; Gidal, Barry E.; Vecht, Charles J.; Schmidt, Dieter
Summary Several commonly prescribed antiepileptic drugs (AEDs)—including phenobarbital, phenytoin, and carbamazepine—stimulate the synthesis of a broad range of monooxygenase and conjugating enzymes. These agents are well known to reduce the duration and action of many lipid‐ and non–lipid‐soluble drugs, including anticoagulants, cytotoxics, analgesics, antiretrovirals, glucocorticoids, statins, antihypertensives, oral contraceptives, psychoactive drugs, immunosuppressants, and of course, other AEDs. This process, therefore, may be associated with a number of clinical problems including higher cancer mortality, progressive AIDS, transplant rejection, and unwanted pregnancy. Withdrawal of enzyme‐inducing AEDs will increase the concentration of induced drugs, bringing with it substantial risk of toxicity if doses are not concomitantly reduced. Yet the potential widespread adverse health consequences of these interactions, both with AED initiation and withdrawal, remain largely underappreciated. Furthermore, induction also affects enzymes involved in endogenous metabolic pathways, and can alter bone biochemistry, gonadal steroids, and lipid markers. Therefore, enzyme‐inducing AEDs may contribute to the development of a number of comorbidities, including osteoporosis, sexual dysfunction, and vascular disease. This process continues as long as the patient takes the inducer. Modern AEDs that do not possess this property have similar efficacy for the common epilepsies. Accordingly, perhaps consideration should be given to starting treatment with, or even switching patients to, non–enzyme‐inducing AEDs.